Study of Ground Water Quality for Irrigation in Near Industrial Area of Bhilwara, Rajasthan (India) - Hussain, J.; Hussain, I.; Ojha, K.G. (Asian Journal of Chemistry, 2010)
47 Ground water samples of 40 villages close to industrial area of Bhilwara town were analyzed for their suitability for irrigation purpose. Ground water of the study area was classified according to Sodium Adsorption Ratio (SAR), Percentage Sodium (PS), Residual Sodium Carbonate (RSC), Kelley's Ratio and Electrical Conductivity. The higher value of electrical conductivity, percentage sodium and Kelley's ratio in some villages indicates the contamination of ground water by industrial effluent resulting in the unsuitability of ground water for irrigation purposes. The value of sodium adsorption ratio indicates that majority of samples falls in low sodium hazard category. As per classification made by Wilcox (1948), on the basis of percentage sodium and electrical conductivity 12 samples are not suitable for irrigation purpose while only 3 samples fall in excellent to good category. The remaining 10 samples fall in good to permissible, 13 samples fall in permissible to doubtful and 9 samples fall in doubtful to unsuitable category. Ground water was also classified according to the classification of United States Salinity Laboratory based on sodium and salinity hazard.